RELEVANSI STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN PADA PT. AKR CORPORINDO, TBK PERIODE 2011-2020 - Erwin Munandar; Hamdan Fathoni (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
The value of the company becomes very important for the company or the holders of stock. Each party has its view on the value of the company, the similarity is to want the value of the company to be in a high position. Managerial ownership is the manager's shareholding where the manager is not only involved in managing the company but also involved in the impact of management decisions. Institutional ownership is the shareholding of another company that has a function as a management supervisor. This examination utilizes unmistakable techniques and quantitative methodologies utilizing optional information upheld by writing and documentation considers. The results showed partially both variables had no significant influence on the value of the company. Similarly, simultaneously it has no significant influence on the value of the company.Keywords: Managerial Ownership, Institutional Ownership, Corporate Value.